The effect of online learning on student engagement: a study conducted with respect to Malaysian university students - Nishantinee, Sathe; Saranya, Krishwasamy; Fun, Terence Zhee Jing; Thivayadarshiny, Ravichandran (2022)
Despite the existence of online learning systems since the early 1990s, it only gained popularity and attention in the Malaysian education system in the wake of the pandemic in early 2020. Online learning has especially posed critical challenges for university students in Malaysia. The objective of this study is to investigate and analyse the online learning factors that affect the engagement level among Malaysian university students. In this research, independent variables (User-friendliness, Course design, Availability of resources, and Digital literacy) are being studied for their significance in student engagement. Three public and three private universities institutions in Malaysia were given a total of 389 sets of questionnaire forms. All of the IVs have a positive corelation with the dependent variable, student engagement, according to the findings of the Person’s correlation coefficient. All IVs, with the exception of user-friendliness, have a clear correlation with the dependant variable according to the analysis of multiple regression. For future research on this topic, it is recommended to expand the population of data by reaching out to more local universities or targeting overseas institutions. Adding on, future researchers should focus on other IVs that have a stronger determinant level of student engagement.